Substituent Effects in Molecular Ruthenium Water Oxidation Catalysts Based on Amide Ligands. Issue 9 (24th February 2017) - Abdel‐Magied, Ahmed F.; Arafa, Wael A. A.; Laine, Tanja M.; Shatskiy, Andrey; Kärkäs, Markus D.; Åkermark, Björn; Johnston, Eric V.
Abstract: The production of clean and sustainable energy is considered as one of the most urgent issues for our society. Mastering the oxidation of water to dioxygen is essential for the production of solar fuels. A study of the influence of the substituents on the catalytic activity of a series of mononuclear Ru complexes (2 a –e ) based on a tetradentate ligand framework is presented. At neutral pH, using [Ru(bpy)3 ](PF6 )3 (bpy=2, 2'‐bipyridine) as the terminal oxidant, a good correlation between the turnover frequency (TOF) and the Hammett σmeta parameters was obtained. Additionally, a general pathway for the deactivation of Ru‐based catalysts2 a –e during the catalytic oxidation of water through poisoning by carbon monoxide was demonstrated. These results highlight the importance of ligand design for fine‐tuning the catalytic activity of water oxidation catalysts. Abstract : R⋅⋅⋅u single? Single‐site Ru complexes are synthesized and evaluated as water oxidation catalysts. The catalytic activity is enhanced by the presence of electron‐donating groups, and a linear relationship between the Hammett parameters of the substituents and the turnover frequencies is established. A general pathway for deactivation of these Ru catalysts during water oxidation through poisoning by CO is also established.